Society in america - Gist, Almon Arthur (My University, 1891)
Introduction: Time has just completed the first chapter in the history of our Republic, 1889 dates one hundred years since the epoch of our federal unite. It was in July, 1778, when the greatest statesmen of colonial times met to consider the policy of declaring themselves free from their mother country. We can see the anxious throng as they crowded around the hall to hear the result of the final vote which meant, to the hopeful, the birth of a nation, to the despondent and heart sick few who feared it would never pass, continued slavery. At two o’clock the messenger rushed out through the open door exclaiming, “It is passed” and the old bell swung to and fro proclaiming liberty to the American people. This was the beginning of our nation’s history. That its growth has been marvelous no one will doubt.
Citation: Gist, Almon Arthur. Society in america. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Independence; History; United States; Colonization; Secession; Society; Theses; Manuscripts (documents)